CONTROLLED DRUG DELIVERY THROUGH MICROENCAPSULATION - NIKHIL K. SACHAN; BHUPENDRA SINGH; K. RAMA RAO (Universiti Sains Malaysia, 2006)
An appropriately designed controlled release drug delivery system can be a major advance towards solving problems concerning to the targeting of drug to a specific organ or tissue and controlling the rate of drug delivery to the target site. The development of oral controlled release systems has been a challenge to formulation scientist due to their inability to restrain and localize the system at targeted areas of gastrointestinal tract. Microparticulate drug delivery systems are an interesting and promising option when developing an oral controlled release system. The objective of this paper is to take a closer look at microparticles as drug delivery devices for increasing efficiency of drug delivery, improving the release profile and drug targeting. In order to appreciate the application possibilities of microcapsules in drug delivery, some fundamental aspects are briefly reviewed.